Power and Empowerment in Higher Education : Studies in Honor of Louis Smith - Robertson, D. B. (Book collections on Project MUSE., 1978)
The tangled relationship of power and higher education is a fascinating one. Where power centers arise on campus, they influence and are influenced by sources of power outside. Students, faculty and administration compete for authority within the academic community; citizens whose education has placed them in a position to obtain social, political, and economic power outside the university walls frequently use it in a way that deeply affects the direction and nature of academic development.